PENGARUH HERD BEHAVIOR DAN HEURISTIC (REPRESENTATIVENESS, ANCHORING, OVERCONFIDENCE, DAN AVAILABILITY BIAS) TERHADAP INVESTMENT DECISION INVESTOR MAHASISWA DI KOTA MALANG - Iman Bramantya Raafifalah (Parsimonia - Jurnal Ekonomi dan Bisnis, 2021)
The capital market is an important part of an economy and can be a means for people to earn profits by investing. The Indonesian capital market is dominated by individual investors and the second-largest occupation is students. Decision making by investors is very vulnerable to errors caused by psychological factors. These factors can be biases that change the way investors analyze information. This study aims to examine and analyze the effect of psychological factors on herd behavior and heuristics (representativeness, anchoring, overconfidence, and availability bias) on the investment decisions of student investors in Malang City. This research was conducted by collecting primary data using a survey of 51 respondents of student investors in Malang City. The data was analyzed using validity and reliability tests, classical assumption test, multiple linear regression, f-test, t-test, and coefficients of determination. The results of this study found that herd behavior and availability bias had a negative effect on investment decisions. This study also found that representativeness, anchoring, and overconfidence have a positive effect on investment decisions.